1997
DOI: 10.1055/s-0038-1656033
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Properties of Rabbit Lungs in Tissue Thromboplastin-induced Intravascular Coagulation

Abstract: SummaryThis study was conducted in order to examine possible anticoagulant properties of the lungs during tissue thromboplastin-induced intravascular coagulation. Rabbit brain tissue thromboplastin (n = 17) or saline (n = 6 + 3) was infused above the right atrium (n = 11 + 3) of the heart or in the arcus aorta (n = 6) for a period of 120 min in non-pregnant New Zealand rabbits. Rabbits infused with tissue thromboplastin responded with significantly (p <0.05) more excessive changes in a number of haemodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In our DIC model, induced by bolus injection of bovine lung thromboplastin, the 4‐h test showed that both DHPC and warfarin significantly inhibited a prolonged PT and APTT, increased fibrinogen levels, decreased FDP and increased platelet count. These findings are consistent with other animal models of DIC studies (Imanishi et al , 1991; Yamazaki et al , 1994; Vad et al , 1997). Gitel and Wessler (1979) reported that warfarin decreased FVII, which inhibited FXa generation, within 6 h in thromboplastin‐induced DIC rats.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our DIC model, induced by bolus injection of bovine lung thromboplastin, the 4‐h test showed that both DHPC and warfarin significantly inhibited a prolonged PT and APTT, increased fibrinogen levels, decreased FDP and increased platelet count. These findings are consistent with other animal models of DIC studies (Imanishi et al , 1991; Yamazaki et al , 1994; Vad et al , 1997). Gitel and Wessler (1979) reported that warfarin decreased FVII, which inhibited FXa generation, within 6 h in thromboplastin‐induced DIC rats.…”
Section: Discussionsupporting
confidence: 93%
“…The combination of a prolonged PT and APTT, low platelet count, decreased fibrinogen and increased FDPs appears to be an adequate indicator of DIC (Baglin, 1996; Vad et al , 1997; Bick, 1998; Levi & Ten Cate, 1999). The PT and APTT are measures of thrombin formation, fibrinogen indicates the efficiency of the fibrinolytic system and the presence of FDP indicates fibrin polymerisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations